Rate of occupancy of Rapid Kuantan buses - Noor Ainina Fazlia, Mohammad (2017)
In Malaysia, the public transport system has always been the government attention to be improved from time to time until government carried out the plan to improve the urban public transport. Public transport should be an incentive for people to move around easily without having to think about traffic congestion. However, people are still choosing to move on their own and do not make use of public facilities. In order to meet the basic needs of urban area and high employment demand, the performance indicators should be addressed. Which is why Rapid Kuantan should comply with several indicators such as bus utilization, time headways, cycle times, passenger ridership, load factor, etc. So, this study aims to assess the rate of occupancy in Rapid Kuantan. 6 bus routes based on short, medium and long route length have been selected to assess the occupancy of Rapid Kuantan bus services and identify routes with low occupancy. Data collections are completed by observing at the bus terminal and doing passenger counting on board the buses of peak and off-peak hour during weekdays and weekend. In this study, the results revealed that for time headway, Hentian Bandar to Ubai recorded the highest time of 70 minutes. Therefore, addition in number of buses can help to reduce the headway between buses. Routes Hentian Bandar to Terminal Sentral Kuantan and Hentian Bandar-Indera Sempurna have high cycle time of 464 and 471 minutes respectively. So, in these kind of cases, it would be better to reduce the waiting time of passenger considering the limited number of buses used. Lastly, routes from Hentian Bandar to Indera Sempurna received high passenger demand for Kuantan area because this routes has obtained 73% of load factor which more higher than the World Bank Standard (70%). Higher load factor than the standard can means that the routes having quite many passenger occupied on the buses but still they able to get seated.